21st Century Discoveries in the Physiology of Adaptation and Dramatic Changes in the Validation of Substance Dependence - D.G, Baitubaev; D, Baitubaeva M. (Jour Med Resh and Health Sci, 2022)
Summary. The article shows that the current level of physiology does not disclose the biological mechanisms of the organism transition from one range to adapt to a higher with an increase in the regular forces of the stimulus above sub-extreme. A new trend in the physiology of adaptation - proqredient adaptation, explains the mechanism of increasing the tolerance of the organism, with dependence on psychoactive substances (PAS ). It is scientifically proved, that dependences of the organism on PAS not the disease, and the states like proqredient (progressive) adaptation.